An advanced Artificial Intelligence platform for a personalised treatment of Eating Disorders - Monaco, Francesco; Vignapiano, Annarita; Piacente, Martina; Pagano, Claudio; Mancuso, Carlo; Steardo, Luca; Marenna, Alessandra; Farina, Federica; Petrillo, Gianvito; Leo, Stefano; Ferrara, Emanuela; Palermo, Stefania; et al. (Frontiers in Psychiatry, 2024)
Eating disor der s (EDs) affect millions wor ldwide. Our innovative Ar tificial Intelligence (AI) -power ed platfor m is designed to impr ove the landscape of EDs diagnosis, tr eatment, and car e accessibility. By lever aging advanced AI technologies, we aim to pr ovide ear lier inter vention and per sonalized ther apy, ultimately leading to significant impr ovements in patient outcomes. This initiative r epr esents a pr omising step for war d in addr essing the challenges posed by EDs and advancing mental healthcar e.